If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -2) + 3(x + 1) = 100 Reorder the terms: 4(-2 + 3x) + 3(x + 1) = 100 (-2 * 4 + 3x * 4) + 3(x + 1) = 100 (-8 + 12x) + 3(x + 1) = 100 Reorder the terms: -8 + 12x + 3(1 + x) = 100 -8 + 12x + (1 * 3 + x * 3) = 100 -8 + 12x + (3 + 3x) = 100 Reorder the terms: -8 + 3 + 12x + 3x = 100 Combine like terms: -8 + 3 = -5 -5 + 12x + 3x = 100 Combine like terms: 12x + 3x = 15x -5 + 15x = 100 Solving -5 + 15x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 15x = 100 + 5 Combine like terms: -5 + 5 = 0 0 + 15x = 100 + 5 15x = 100 + 5 Combine like terms: 100 + 5 = 105 15x = 105 Divide each side by '15'. x = 7 Simplifying x = 7
| 3p-4=10 | | 3x+2=42 | | x(x+2)=159+6(x+x+2) | | 8=3x^2-2x | | 8=3x*3x-2 | | X=3+0.25x | | X=3+0.25 | | 3Q=2P-M | | 2x-4u-5=0 | | (343)1/4(343)-1/12 | | 3(2p-7)=4p-5 | | f(-3)=-3 | | 8X+14=38+2x | | 8X+14=38+2 | | h^2-2h=0 | | 2x+3=10-3x | | 1/2X7 | | 10x-4=5x+15 | | 12-(-y-19)=12 | | 5z^2-4z^4-4=0 | | x=(5x-6)+21 | | 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 |